Optical solitons with differential group delay for complex Ginzburg–Landau equation - Yakup Yıldırım; Anjan Biswas; Anwar Ja’afar Mohamad Jawad; Mehmet Ekici; Qin Zhou; Abdullah Kamis Alzahrani; Milivoj R. Belic (Results in Physics, 2020)
This paper addresses optical solitons in birefringent fibers that is modeled by complex Ginzburg–Landau equation with Kerr law nonlinearity. Three forms of integration architecture retrieves soliton and other solutions to the model. The solitons are classified and their existence criteria are also presented.